The Influence of the Use of Information Technology on Employee Performance in Class I Correctional Institutions in Makassar - Lili Monica; Jamaluddin Jamaluddin; Sitti Hardiyanti Arhas (ASHA Publishing, 2026)
Employee performance reflects how well the goals of an agency or institution have been achieved, including aspects of quality, quantity, accuracy, work results, and level of independence. Therefore, this study was conducted to examine the influence of information technology on the performance of employees in the Makassar Class I Correctional Institution. The study uses a quantitative approach with bivariate analysis. The findings of the study show that the indicators of the variables of information technology and employee performance are in a very satisfactory category. The results of the product moment correlation analysis indicate a strong relationship between the use of information technology and the level of employee performance. In addition, the results of simple linear regression strengthen these findings by showing the positive and significant influence of information technology on employee performance. Quantitatively, the use of information technology in the Makassar Class I Correctional Institution achieved a score of 90%, while employee performance achieved a score of 96%; both scores fall within the very satisfactory category. Information technology recorded a 59.1% contribution to employee performance. Thus, the results of this study offer an in-depth look at the importance of the application of information technology in improving the quality of employee performance in correctional institutions, as well as providing a strong basis for the formulation of more appropriate and strategic policies in the future. This study not only provides empirical evidence of the positive influence of information technology on employee performance but also highlights the unique context of correctional institutions as a public service environment where digitalization faces structural and cultural barriers. The results have influenced the development of ICT-based performance management in the public sector, especially in correctional administration.